The Philosophical Dimensions of Islamic Religious Education (PAI) As A Basis for The Ethical Response to Artificial Intelligence: A Qualitative Study at SDI Az-Zahrah Palembang - Waliya Purnama Sari; Syarip Syarip; Kasinyo Harto; Mardiah Astuti; Sodikin Sodikin (FKIP - Universitas Riau, 2026)
This research empirically examines the philosophical dimensions of Islamic Religious Education (PAI), namely ontology, epistemology, and axiology, to develop an ethical foundation for the presence of Artificial Intelligence (AI) in elementary schools. This study is urgent due to government policies mandating Coding and AI (KKA) lessons and the limited philosophical PAI studies on AI. The study employs an interpretive phenomenological qualitative approach at Az-Zahrah Islamic Elementary School in Palembang, which adheres to Maqāṣid al-Sharī‘ah (specifically Ḥifẓ al-Dīn and Ḥifẓ al-‘Aql). Data were collected through interviews, non-participant observation, and document analysis. The main findings are structured by dimension: 1) Ontologically, PAI positions AI as an inanimate tool (a non-divine creation), maintaining Ḥifẓ al-Dīn (rejecting AI authority) and Ḥifẓ al-'Aql (viewing AI as a human intellectual extension). 2) Epistemologically, PAI establishes the Qur'an and Hadith as the ultimate ethical filters for AI algorithmic information and emphasizes citing sources (plagiarism is considered ghishsh). 3) Axiologically, PAI uses the principles of maṣlaḥah (greatest good) and mas'uliyah (full user moral responsibility) as a moral compass, rejecting technological determinism. The PAI philosophical framework successfully serves as an adaptive and critical ethical basis for AI, aiming to produce a competent, reflective, and responsible generation aligned with Islamic values.